+0  
 
0
42
1
avatar

how to do -4(y+6)=32

Guest Oct 30, 2017

Best Answer 

 #1
avatar+5258 
+1

-4(y + 6) =  32

                             Divide both sides of the equation by  -4 .

y + 6  =  32 / -4

 

y + 6  =  -8

                            Subtract  6  from both sides.

y  =  -8 - 6

 

y  =  -14

hectictar  Oct 30, 2017
Sort: 

1+0 Answers

 #1
avatar+5258 
+1
Best Answer

-4(y + 6) =  32

                             Divide both sides of the equation by  -4 .

y + 6  =  32 / -4

 

y + 6  =  -8

                            Subtract  6  from both sides.

y  =  -8 - 6

 

y  =  -14

hectictar  Oct 30, 2017

13 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details